Investment Decision Making: A study of Individual Investors Perception - Onsiro, Martin Ronald; Ombati, Robert Mosomi (International Journal For Research In Business, Management And Accounting, 2019)
Investment culture among the people of a country is an essential prerequisite for capital formation and the faster growth of an economy. Investment culture refers to the attitudes, perceptions and willingness of the individuals and institutions in placing their savings in various investment alternatives. There is vast change in the socio-economic and psycho-graphic profile of the Indian investors. The term investment is used to describe the process of investing money in shares, debentures, fixed deposits, gold, real assets, life policies, mutual funds and money market instruments etc. By investing, an investor commits the present funds to one or more assets to be held for some time in expectation of some future return in terms of interest (revenue) or capital gain. Individual investors consider a number of factors before deciding to invest their funds in various securities involving varying degrees of risk and return. In the present economic scenario, the options available to them are different and the factors motivating the investors to invest are governed by their socio-economic profile. A study on the investors’ perceptions and preferences, thus assumes a greater significance in the formulation of policies for the policies for the development and regulation of investment plans in general and protection of Indian investors. Exploratory research is used for the study. Data was collected through primary and secondary sources. Questionnaire has been designed to collect primary data. Samples of 100 respondents have been taken through convenience sampling process.